Prevalence and Clinical Characteristics of Bacterial Pneumonia in Neurosurgical Emergency Center Patients: A Retrospective Study Spanning 13 Years at a Tertiary Center - Weijian Yang; Haijun Yao; Caihua Xi; Xiangru Ye; Qifang Chen; Jun Zhang; Jian Yu; Jin Hu (Microorganisms, 2023)
Patients with brain injuries are at a heightened susceptibility to bacterial pneumonia, and the timely initiation of empiric antibiotic treatment has been shown to substantially reduce mortality rates. Nevertheless, there is a need for knowledge regarding the resistance and prevalence of pulmonary bacterial infections in this patient population. To address this gap, a retrospective study was conducted at a neurosurgical emergency center, focusing on patients with brain injuries. Among the entire patient population, a total of 739 individuals (18.23%) were identified as having bacterial pneumonia, consisting of 1489 strains of Gram-negative bacteria and 205 strains of Gram-positive bacteria. The resistance of Klebsiella pneumoniae to imipenem exhibited a significant increase, rising from 21.74% in 2009 to 96.67% in 2018, and subsequently reaching 48.47% in 2021. Acinetobacter baumannii displayed resistance rates exceeding 80.0% against multiple antibiotics. The resistance profile of Pseudomonas aeruginosa was relatively low. The proportion of Staphylococcus aureus reached its peak at 18.70% in 2016, but experienced a decline to 7.83% in 2021. The abundance of Gram-negative bacteria exceeded that of Gram-positive bacteria by a factor of 5.96. Klebsiella pneumoniae, Acinetobacter baumannii, and Staphylococcus aureus are prominent pathogens characterized by limited antibiotic choices and scarce treatment alternatives for the isolated strains.